Detection of splicing forgery using differential evolution and wavelet decomposition. (20th November 2019) - Kashyap, Abhishek; Suresh, B; Gupta, Hariom
Abstract: In this paper, we have proposed a computationally efficient algorithm to detect splicing (copy-create) forgery, our proposed method is developed by using differential evolution and wavelet decomposition, the differential evolution algorithm automatically generates customized parameter values of tampered images, and wavelet decomposition is used to process large-size images under block-based framework. Our proposed method is resilient to distortions, such as the addition of Gaussian noise, scaling and compression of the forged images.